Measuring Self-Efficacy in English for Specific Purposes: A Case Study of Engineering Students - Diana, Apriana (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2025)
This descriptive statistical study assesses students' perceptions of their self-efficacy in English for Specific Purposes (ESP). The study involved 40 students from the Mechanical Engineering program at the Faculty of Engineering, Universitas Muhammadiyah Jakarta. Data were collected using a 5-point Likert scale questionnaire, adapted and modified from Kosimov (n.d.), and distributed via Google Forms after undergoing face validity assessment. The data were analyzed using simple percentage calculations and presented descriptively. The findings indicate that the majority of students held a positive perception of their self-efficacy in ESP, as evidenced by the highest response rate for the